An updated insight into the Sialotranscriptome of Triatoma infestans: developmental stage and geographic variations. - Alexandra Schwarz; Nora Medrano-Mercado; Günter A Schaub; Claudio J Struchiner; M Dolores Bargues; Michael Z Levy; José M C Ribeiro (Public Library of Science (PLoS), 2014)
Triatoma infestans is the main vector of Chagas disease in South America. As in all hematophagous arthropods, its saliva contains a complex cocktail that assists blood feeding by preventing platelet aggregation and blood clotting and promoting vasodilation. These salivary components can be immunologically recognized by their vector's hosts and targeted with antibodies that might disrupt blood feeding. These antibodies can be used to detect vector exposure using immunoassays. Antibodies may also contribute to the fast evolution of the salivary cocktail.Salivary gland cDNA libraries from nymphal and adult T. infestans of breeding colonies originating from different locations (Argentina, Chile, Peru and Bolivia), and cDNA libraries originating from F1 populations of Bolivia, were sequenced using Illumina technology. Coding sequences (CDS) were extracted from the assembled reads, the numbers of reads mapped to these CDS, sequences were functionally annotated and polymorphisms determined.Over five thousand CDS, mostly full length or near full length, were publicly deposited on GenBank. Transcripts that were over 10-fold overexpressed from different geographical regions, or from different developmental stages were identified. Polymorphisms were mapped to derived coding sequences, and found to vary between developmental instars and geographic origin of the biological material. This expanded sialome database from T. infestans should be of assistance in future proteomic work attempting to identify salivary proteins that might be used as epidemiological markers of vector exposure, or proteins of pharmacological interest.